Essays on institutional investments - Li, Dan (2024)
Institutional investors play a crucial role in leveraging their advantages in obtaining market information and professional knowledge for corporate operations. While there have been numerous studies on institutional investors, the distinctive background of China, characterised by its concentrated ownership structure and strong governmental control, calls for further investigation. Notably, recent government focus on relaxing restrictions on financial institutions' investment activities has significantly altered the investment strategies of institutional investors, consequently changing their management of firms that they hold shares. Furthermore, the distinct government ownership in the Chinese market may expose companies to significant political interference, potentially driving managers to make corporate decisions that prioritise political goals over economic efficiency. Collectively, an in-depth investigation on the roles of institutional investors in the context of China is necessary. In this thesis, our study contributes to a deeper understanding of the interactions between institutional investors, corporate governance, and firm performance.